Continuous Renal Replacement Therapy Using Membranes with Increased Adsorption Capacity in Patients with Septic Shock after Neurosurgical Interventions - А. I. Burov; T. А. Аbramov; N. V. Kurdyumova; А. V. Oshorov; D. S. Korotkov; N. S. Kostritsa; G. V. Danilov; Yu. V. Strunina; I. А. Savin (Вестник анестезиологии и реаниматологии, 2022)
Introduction. The combination of primary brain injury with cytokine storm and hemodynamic disturbance in septic shock leads to secondary brain damage and growing neurological deficit. Blood purification procedures can be considered as an additional option in the treatment of septic shock in this group of patients.Subjects and Methods. The study included 11 patients after neurosurgical interventions with septic shock and acute kidney injury who underwent continuous renal replacement therapy (CRRT) using membranes with increased adsorption capacity.Results. During CRRT there was a significant regression in severity of multiorgan dysfunction according to SOFA score, a decrease in the requirement for vasopressor support with norepinephrine, and a decrease in lactate blood level. In addition, after the end of the procedure, there was a significant decrease in procalcitonin blood level. Septic shock reversal was observed in 8/11 patients (72.7%). In 3/11 patients, neurological deficits regressed during the procedure.Conclusions. The results indicate the possibility of using CRRT with membranes with increased adsorption capacity in patients after neurosurgical interventions with septic shock. Changes in neurological status can be considered as an additional parameter for the effectiveness of therapy for septic shock in patients with primary brain injury.